PERANAN BALAI KERAPATAN TINGGI PADA MASA KERAJAAN SIAK TAHUN 1889-1908 - Lasmi Purnama Sari; Prof. Dr. Isjoni, M.Si '; Drs. Kamaruddin, M ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Balai Kerapatan Tinggi named Balai Rung Seri is building that was builtduring the reign of Sultan royal Siak. Balai Kerapatan Tinggi is a building that was built during the reight of sultan Siak kingdom. Balai Kerapatan Tinggi used for deliberation and the judiciary in resolving the existing problems in the Kingdom Siak. This is evident during the Sultan Assyaidis Syarif Hasyim Abdul Jalil Syaifuddin, Balai Kerapatan Tinggi very important role in regulating goverment. As for the purpose of this study was to determine the background of the establishment of the Balai Kerapatan Tinggi at the time of the Sultan Sultan Assyaidis Syarif Hasyim Abdul Jalil Syaifuddin, to know the purpose ot the establishment of centers, to know the role of the Balai Kerapatan Tinggi at the time of the Sultan Assyaidis Syarif Hasyim Abdul Jalil Syaifuddin, to know the officer or the person great royal Balai Kerapatan Tinggi Siak play roles in the future Sultan Assyaidis Syarif Hasyim Abdul Jalil Syaifuddin. The method used in this study is the historical method and qualitative method. Where the data were collected through interviews, documentation, and literature. Data was analyzed using qualitative way. As for the location of research that Kecamatan Siak Kabupaten Siak Provinsi Riau. When research started from the seminar proposal to thethesis examination. The result showe that the Balai Kerapatan Tinggi was first builth during Sultan Assyaidis Syarif Hasyim Abdul Jalil Syaifuddin.these centers play an important role in the Kingdom Siak, which is used to place the trial, the coronation of the king and ceremonies led by the royal Sultan Siak. To run the goverment assited the great Sultan royal Siak.Key Words: Balai Kerapatan Tinggi, Royal, Siak